(3GdJLhjO dHZjI GdeRjOs - (3YHO GdQMef Hf YJjb Hf Nda GdUbdj GdbQTj, CHh GdbGSe, GdeYQha H` GHf GdaMGe,J (B516 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYGde ebGOjQ GdCehQ GdeWdY Ydi eVeQGJ GdUOhQ GdSGHb aj GdCTjGA GeQg GdeGVj ajgG s
(3BNQgG (B:s
(3hbO fLRJ GdbQGAGJ GdSHY Ydi eGQSeJ hjONdfG hEjGc LfGJ GdfYje Je cJGH GdJLQjO HYhf Gddg Gdedc s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3aj GdbQGAJ GdSHYs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs